Characteristics Analysis of Bio-Based Silica Extracted from Sarawak Palm Oil Waste - Nur Amalina Shairah Abdul Samat, Nur; Aishah Zulkafly, Siti; Zulaikha Kamarul Jaman, Ummie; Syuhada Ahmad Zauzi, Nur; Rezaur Rahman, Md; Baini, Rubiyah (International Journal of Engineering and Technology, 2018)
Due to high production of palm oil, surplus quantities of palm oil wastes such as empty fruit bunches (EFB) and palm kernel shells (PKS) are generated. This study aims to analyze the characteristics of EFB and PKS ashes and their respective bio-silica content when combusted at different temperatures; 400°C, 600°C and 800°C. Several tests like weight loss, colour and Fourier Transform Infrared (FTIR) analysis are conducted. EFB records higher weight loss compared to PKS for all combustion temperatures, thus implying less silica content compared to the later. Both wastes also show the highest weight loss at 99.20% and 98.51% respectively, when they are burnt at 800°C than those combusted at lower temperatures. This happens because more impurities evaporate at 800°C, thus resulting in greater relative amount of silica in the ash. Colour analysis shows that the whiteness of both EFB and PKS ashes are the highest when combustion occurs completely at 800°C, particularly at 71.56 and 42.40 respectively. Besides, FTIR analysis depicts distinct presence of Si-O and Si-O-Si functional groups in both EFB and PKS ashes for all temperatures. It is also shown that combustion at 400°C are insufficient to remove impurities like hydroxyl groups, CH2 components and organic compounds.